Hypoxia-responsive polymeric nanoparticles for tumor-targeted drug delivery - Thambi, Thavasyappan; Deepagan, V. G.; Yoon, Hong Yeol; Han, Hwa Seung; Kim, Seol-Hee; Son, Soyoung; Jo, Dong-Gyu; Ahn, Cheol-Hee; Suh, Yung Doug; Kim, Kwangmeyung; Kwon, Ick Chan; Lee, Doo Sung; et al. (ELSEVIER SCI LTD, 2014)
Hypoxia is a condition found in various intractable diseases. Here, we report self-assembled nanoparticles which can selectively release the hydrophobic agents under hypoxic conditions. For the preparation of hypoxia-responsive nanoparticles (HR-NPs), a hydrophobically modified 2-nitroimidazole derivative was conjugated to the backbone of the carboxymethyl dextran (CM-Dex). Doxorubicin (DOX), a model drug, was effectively encapsulated into the HR-NPs. The HR-NPs released DOX in a sustained manner under the normoxic condition (physiological condition), whereas the drug release rate. remarkably increased under the hypoxic condition. From in vitro cytotoxicity tests, it was found the DOX-loaded HR-NPs showed higher toxicity to hypoxic cells than to normoxic cells. Microscopic observation showed that the HR-NPs could effectively deliver DOX into SCC7 cells under hypoxic conditions. In vivo biodistribution study demonstrated that HR-NPs were selectively accumulated at the hypoxic tumor tissues. As consequence, drug-loaded HR-NPs exhibited high anti-tumor activity in vivo. Overall, the HR-NPs might have a potential as nanocarriers for drug delivery to treat hypoxia-associated diseases. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; CANCER-THERAPY; POLY(ETHYLENE GLYCOL); FLUORESCENT MARKERS; BLOCK-COPOLYMERS; CELLS; DOXORUBICIN; CAMPTOTHECIN; MECHANISMS; CONJUGATE